EP1296 The technique of sentinel lymph node and afferent lymphatic channel detection in radicality reducing early stage cervical cancer surgery. (1st November 2019) - Hruda, M; Robová, H; Halaska, MJ; Pichlík, T; Rob, L
Abstract : Introduction/Background: In our video we would like to demonstrate the technique of identification of sentinel lymph nodes and afferent lymphatic channels in paracervix using the combination of Tc radiocolloid and Patent Blue in patients with early stage cervical cancer. Methodology: The patients included in this study were diagnosed with early stage spinocellular or adenocarcinoma of uterine cervix stage IA and IB1 up to 2 cm maximal diameter with maximal depth of invasion of less than half of the stroma. We use an ultrashort protocol consisting of application of 2 ml Tc (20 MBq) and 2 ml of Patent Blue diluted in 2 ml of saline. Tc is applicated in surgical theatre at the beginning of anaesthesia using 4 quadrant technique followed by the application of 1 ml Patent Blue into each quadrant. The surgical extirpation was performed in interval of 12 to 15 minutes after the application. Results: During the period 2009–2018 we included 123 women. In this group we detected positive sentinel lymph nodes in 6 cases. The detection rate (DR) of sentinel lymph nodes was 122/123–99, 2%, specific side detection rate (SSDR) 232/244–95, 1% Our aim was to detect 246 channels in 123 women. No channels were detected in 6 women (4.9%), unilateral channel was detected in 25 women (20, 3%) and bilateral channels were detected in 93 cases (75, 6%). Conclusion: Our video illustrates the safe technique of identifying and extirpation of sentinel nodes and afferent channels in the paracervix. In early stages of cervical cancers this technique can achieve very good detection rate of sentinel nodes on both sides of the pelvis. Work was supported Charles University research program PROGRES Q 28 (Oncology). Disclosure: Nothing to disclose